2021
DOI: 10.3390/s21165559
|View full text |Cite
|
Sign up to set email alerts
|

Technology CAD (TCAD) Simulations of Mg2Si/Si Heterojunction Photodetector Based on the Thickness Effect

Abstract: Research on infrared detectors has been widely reported in the literature. For infrared detectors, PbS, InGaAs, PbSe, InSb, and HgxCd1-xTe materials are the most widely used and have been explored for photodetection applications. However, these are toxic and harmful substances which are not conducive to the sustainable development of infrared detectors and are not eco-friendly. Mg2Si is a green, healthy, and sustainable semiconductor material that has the potential to replace these toxic and damaging photoelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…After determining the most optimal texturing, passivation and Si overgrowth conditions to obtain Si-compatible templates for HSC development, we focused on the formation of the Mg 2 Si-based solar light absorbing layer. On one hand, Mg 2 Si possesses outstanding optoelectronic properties to be applied as a VIS-NIR light absorber and photodetector with high Si-compatibility [ 46 , 47 , 48 , 49 , 50 , 51 ]. On the other hand, we have already demonstrated that silicidation of the textured Si surface such as b-Si with magnesium resulted in a new wide band optical absorber called “black silicide” [ 29 ], demonstrating a very high PV potential.…”
Section: Resultsmentioning
confidence: 99%
“…After determining the most optimal texturing, passivation and Si overgrowth conditions to obtain Si-compatible templates for HSC development, we focused on the formation of the Mg 2 Si-based solar light absorbing layer. On one hand, Mg 2 Si possesses outstanding optoelectronic properties to be applied as a VIS-NIR light absorber and photodetector with high Si-compatibility [ 46 , 47 , 48 , 49 , 50 , 51 ]. On the other hand, we have already demonstrated that silicidation of the textured Si surface such as b-Si with magnesium resulted in a new wide band optical absorber called “black silicide” [ 29 ], demonstrating a very high PV potential.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their low bandgap energy (1.12 eV), Si PDs have a narrow spectrum range with a response cut-off at 1100 nm [3,[4][5][6]. The photo response cut-off wavelength of conventional Si PDs can be increased to more than 1100 nm by fabricating heterojunction PDs with a detection wavelength range of 400 to 1500 nm out of the environmentally benign semiconductor material Mg 2 Si [7]. The earth's crust is rich in C, Mg, and Si, which are non-toxic and devoid of pollution and exhibit qualities that support sustainable development.…”
Section: Introductionmentioning
confidence: 99%